Sensory evaluation of biscuits enriched with artichoke fiber‐rich powders (Cynara scolymus L.) - San José, Francisco J. (Food Sci Nutr, 2017)
The artichoke by‐products from the canning industry are mainly used for silage, being minimally revaluated. The ways of extraction of by‐products of artichoke into fiber‐rich powders modify their industrial applications in biscuits, as the sensory evaluation may change compared with the reference fiber (Pea fiber, P) used with commercial biscuit. In this sensory study biscuits enriched with fiber‐rich powders of artichoke (W, Ca) are compared with biscuits with the same percentage of the reference fiber (P) and control biscuits without fiber (B). For most of the sensory attributes of the biscuits enriched with artichoke fiber‐rich powders were perceived similar to the biscuits with the commercial reference fiber (P). The good sensory behavior of the biscuits with artichoke fiber‐rich powders during two storage conditions applied may confirm that the artichoke by‐products would be a suitable substitute for pea fiber in oven‐baked products, like wholemeal biscuits with high‐fiber content.